Man caves, granny flats and alternative living spaces: Low carbon home retrofit and implications for policymaking. (May 2022) - Middha, Bhavna; Robertson, Sarah; Willand, Nicola; Horne, Ralph
Abstract: This paper presents new insights into low carbon home retrofit by highlighting home improvement practices to spaces beyond the main dwelling. We use social practice theories and draw on empirical research with householders in Australia focused on practices of homemaking in man caves, garages and granny flats to trace negotiations and relations between spaces, practices and the governance of retrofit. In doing so, we understand the adaptation of what are often considered 'outside' or 'uninhabitable' spaces as alternative lived spaces, or alternative retrofit spaces. The paper argues that studying the textures, or socio-spatial-material relationships of these alternative retrofit spaces helps understand how unexpected trajectories of future energy use are established. The research problematises policy making and related interventions that treat material dwelling upgrades in binary ways, such as 'outside/inside' and/or 'habitable/uninhabitable'. Retrofit governance is shown to extend across various scales such as urban planning and consumption of small appliances, across space and time, and shaped by traditional values and inclusiveness in the community. The research highlights the informal homemaking practices that mean retrofit governance traverses both formal and informal aspects. Retrofit and urban policies may need to take these aspects into account in terms of regulations and strategies, but also as they relate to larger social change interventions focused on understandings, experiences and end goals.